Islamic finance: financial inclusion or migration? - Ahmed Tahiri Jouti (ISRA International Journal of Islamic Finance, 2018)
Purpose: This paper aims to define a methodology to assess the impact of introducing Islamic finance on financial inclusion. Design/methodology/approach The paper is based on a literature review to understand the link between Islamic finance and financial inclusion. The second part of the paper presents a conceptual framework to assess the impact of introducing Islamic finance on financial inclusion in a defined context based on the profiling of people interested in Islamic finance. Findings The paper brings an insight on the impact of introducing Islamic finance. Indeed, it could cause a financial migration to Islamic banks that can take many forms and depends on many factors that call for deep analysis. Research limitations/implications The paper would help financial authorities and financial institutions to measure the impact of introducing Islamic finance on their businesses and the stability of the whole system. Practical implications Islamic finance can not only enhance financial inclusion but also create financial migration. The two implications can vary from one context to another. Locial implications Islamic finance can contribute in the effort of including 'self-excluded' people with religious concerns as well as people without access to financial services. Originality/value This paper promotes the idea that Islamic finance is not exclusively a way to enhance financial inclusion.
Keywords: 330; Financial inclusion; Financial migration; Islamic finance; Lack of access; Self-exclusion; Unbanked people